Mitochondria and bacterial pathogens. - Marchi, Saverio; Galluzzi, Lorenzo (International review of cell and molecular biology ;, 2023)
Mitochondria and Bacterial Pathogens, Volume 374, Part A. Mitochondria control various processes that are integral to cellular and organismal homeostasis, including Ca2+ fluxes, bioenergetic metabolism, and cell death. Perhaps not surprisingly, multiple pathogenic bacteria have evolved strategies to subvert mitochondrial functions in support of their survival and dissemination. In the IRCMB volume 375, the authors discus different pathogenic mechanisms that converge on the ability of bacteria to control the mitochondrial compartment of host cells. Collection of articles reporting the role of mitochondria during bacterial infection Mitochondria, the evolutionary successors of an ancient endosymbiotic prokaryote, occupy a central position in the biology of modern eukaryotic cells Numerous pathogenic bacteria have evolved strategies to subvert the mitochondrial functions of host cells in support of proliferation and dissemination.